Information System for Monitoring Production Process of Dried Kelor Leaf Dried Using the FAST Method - Sudiarsa, I Wayan; Sudipa, I Gede Iwan; Sugiartawan, Putu; Maharianingsih, Ni Made; Pande, Ni Kadek Nita Noviani (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Moringa or Kelor leaves, rich in nutrients and health benefits, are used in many culinary, supplement, and medicinal items. However, drying moringa leaves is a crucial step that impacts product quality. Companies must maintain product quality and production efficiency to meet rising demand. Since moringa leaf drying production management is difficult, this study uses the Framework for the Application System Thought (FAST) method. Its use in moringa drying allows thorough monitoring of temperature, humidity, drying duration, and other product quality factors. According to this research, using the FAST method in the moringa leaf drying production management monitoring application will help identify production issues, prevent product damage, and improve product quality. This research improves moringa production management and helps explain FAST method implementation in industrial process management. FAST is significant for monitoring applications because it can continually monitor all production conditions that affect drying moringa leaves. FAST can immediately detect dryer humidity issues. The FAST technique and moringa drying production management monitoring applications can be used to improve product quality, operational efficiency, and consumer safety in this research. Thus, this research gives tangible answers for the moringa processing business and can be applied to other industrial sectors facing comparable production process management issues.